REPRODUCING OR RESISTING? WRITING CENTRE TUTORS, AI TOOLS, AND THE REMAKING OF THE ACADEMIC WRITING FIELD - Adedokun, Theophilus; Mheta, Gift (Faculty of Administrative Science, Universitas Brawijaya, 2026)
The integration of generative artificial intelligence into higher education writing support has introduced significant complexities for writing centre peer tutors, particularly within the massified university contexts characteristic of post-apartheid South Africa. This study, nested within a broader project Reimagining Writing Centre Pedagogy in the Age of AI: Exploring Digital Tutoring Practices, Epistemic Access, and Student Support in Massified Higher Education navigate the pressures that AI-mediated tutoring exerts on collaborative, student-centred pedagogy. Employing a qualitative case study design, the study generated data through semi-structured interviews with nine peer tutors, analysed using reflexive thematic analysis and theorised through Pierre Bourdieu’s conceptual triad of habitus, capital, and field. Three interconnected themes emerged: tutors experienced a condition of hysteresis as their deeply held pedagogical commitments to student voice and authentic writing collided with a student culture oriented toward AI-mediated efficiency; differential AI access reproduced and deepened pre-existing socioeconomic inequalities among students; and digital platforms simultaneously extended the reach of writing centre support and generated new barriers for disadvantaged students. The study concludes that tutor responses constitute neither straightforward reproduction nor clean resistance to existing field logics, but an adaptive remaking of writing centre pedagogy, with significant implications for equity-centred policy and practice in massified higher education.